Current antibacterial therapy for ocular burns (Ukrainian Journal of Ophthalmology, 2026)
Background: Since ocular infection is common following ocular burns, and may lead to severe infectious complications like corneal ulcers, infiltrates and abscesses, prevention and treatment of these complications has been always important.Purpose: To investigate the nature of the microflora cultured from ocular burn patients and the sensitivity of this microflora to current antibacterial agents.Materials and Methods: We investigated conjunctival microflora from 184 ocular burn patients (224 eyes) at different time points following ocular burns. In total, 559 cultures were performed. Antibacterial and antiseptic agents under investigation included ciprofloxacin (Floximed), ofloxacin, levofloxacin (Levofloximed), moxifloxacin, gentamycin, tobramycin (Tobrimed), futaron, octenisept and betadine.Results: Microflora was cultured from 88% of the conjunctival samples examined. Staphylococcus epidermidis was the most commonly cultured organism (54.2%), followed by Staphylococcus aureus (14.3%), Escherichia coli (7.6%), Enterococci (5.6%), fungi (3.0%), Staphylococcus haemolyticus (2.5%), Pseudomonas aeruginosa (1.5%), and Streptococcus haemolyticus (0.4%). No organisms were isolated from 12% of the conjunctival microflora samples. The sensitivity of these microorganisms to each of the antibacterial agents under investigation was determined. Levofloxacin (Levofloximed), ciprofloxacin (Floximed), moxifloxacin, ofloxacin, gentamycin, and tobramycin (Tobrimed) demonstrated high antibacterial activity against the organisms.Conclusion: Following ocular burns, conjunctival microflora always contains organisms that can cause various infectious complications. Administration of antibacterial medications for prevention and treatment of infectious complications should be based on the sensitivity of the organisms to these medications. Prior to obtaining the results of sensitivity analyses of cultured microorganisms, or if such tests are unavailable, broad spectrum antibiotics, ? fluoroquinolones (moxifloxacin, levofloxacin (Levofloximed), and ciprofloxacin (Floximed)) and aminoglycosides (gentamycin and tobramycin (Tobrimed)) ? should be administered.If the microorganism exhibits no sensitivity to antibiotics, such antiseptics as octenisept or betadine may be administered.
Keywords: ocular burns; microflora; antibacterial therapy